Clotho: Proactive wearout deceleration in Chip-Multiprocessor interconnects - Vitkovskiy, Arseniy; Soteriou, Vassos; Gratz, Paul V. (My University, 2015)
With advancing process technology, Chip-Multiprocessors (CMPs) are experiencing ever worsening reliability due to prolonged operational stresses. The network-on-chip that interconnects the components of CMPs is especially vulnerable to such wearout-induced failure. To tackle this ominous threat we present Clotho, a novel, wearout-Aware routing algorithm. Clotho continuously considers the stresses the on-chip interconnect experiences at runtime, along with temperature and fabrication process variation metrics, steering traffic away from locations that are most prone to Electromigration (EM)-and Hot-Carrier Injection (HCI)-induced wear. Under realistic workloads Clotho yields 66% and 8% average increases in mean time to failure for EM and HCI, respectively.
Keywords: Human computer interaction; Transistors; Routing; Stress; Electromigration; Correlation; Integrated circuit interconnections